TI_GERICHTE 32.2005.241 vom 20. Oktober 2006 , Effetti temporali di una decisione (in concreto decorrenza della rendita). - TI Tribunale d'appello (2006)
Effetti temporali di una decisione (in concreto decorrenza della rendita).